Effect of polyacrylonitrile fiber on the properties of alkali-activated ceramic/slag-based mortar. (December 2021) - Gaibor, Norma; Leitão, Dinis; Miranda, Tiago; Cristelo, Nuno; Pereira, Eduardo N.B.; Cunha, Vítor M.C.F.
Abstract: This study aims to optimize the mechanical behavior of alkali-activated mortar reinforced with polyacrylonitrile fibers. In order to accomplish this, ceramic waste from clay bricks and roof tiles was used as the primary precursor, which was then combined with ladle furnace slag and activated with sodium silicate. Thereby, fibers were added to improve its brittle behavior, namely its toughness and the residual flexural strength of the material, thus enabling its use in a myriad of applications within the construction sector. So, an extensive experimental campaign was carried out to assess the influence of polyacrylonitrile fibers content (0%, 0.5%, and 1% in volume) and the curing time (14, 28, and 90 days) on the main physical and mechanical properties, including capillarity, porosity, uniaxial compressive, and flexural strength. Microstructural analysis was accomplished with Scanning Electron Microscopy, X-ray Energy Dispersive Analyzer, X-ray diffraction, and Fourier Transform Infrared Spectroscopy. Experimental results of the developed mortars showed satisfactory mechanical properties, enhanced by the fibers, regardless of the fiber ratio added, attaining compressive and tensile under flexural strengths' values up to 47 MPa and 7 N/mm 2, respectively, after 90 days of curing. Compared to non-reinforced mortars, these values represent an improvement of about 20% in both cases, thus justifying the addition of fibers. Highlights: Alkali-activated CW/LFS-based mortar was reinforced with PAN fibers. Fiber addition positively affected the mechanical performance of the AAm. Workability needs further testing, so that the fiber content can be increased.